2014
DOI: 10.1016/j.neuron.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Roles for Primate Frontal and Parietal Cortex in Guarding Working Memory from Distractor Stimuli

Abstract: Prefrontal cortex (PFC) and posterior parietal cortex are important for maintaining behaviorally relevant information in working memory. Here, we challenge the commonly held view that suppression of distractors by PFC neurons is the main mechanism underlying the filtering of task-irrelevant information. We recorded single-unit activity from PFC and the ventral intraparietal area (VIP) of monkeys trained to resist distracting stimuli in a delayed-match-to-numerosity task. Surprisingly, PFC neurons preferentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 50 publications
9
108
1
Order By: Relevance
“…Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes. Similar results have been reported repeatedly for numerosity-selective neurons in monkeys (10)(11)(12)(13)(14)(15)(16)(17)(18). Third, both the neuronal and the behavioral tuning functions were best described on a logarithmic number line, arguing for a nonlinearly compressed coding of numerical information.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes. Similar results have been reported repeatedly for numerosity-selective neurons in monkeys (10)(11)(12)(13)(14)(15)(16)(17)(18). Third, both the neuronal and the behavioral tuning functions were best described on a logarithmic number line, arguing for a nonlinearly compressed coding of numerical information.…”
Section: Discussionsupporting
confidence: 83%
“…Our behavioral and neuronal data show an impressive correspondence of neuronal mechanisms found in the avian brain with those reported earlier in the nonhuman and human primate brain: First, NCL neurons were tuned to individual preferred numerosities characteristic of a "labeled-line code," enabling an unequivocal representation of numerosity by a neuronal population. Complementary findings have been made in the monkey prefrontal and posterior parietal cortex; both in the highly trained (10)(11)(12)(13)(14)(15)(16)(17)(18) and in the numerically naïve monkey (30), numerosity is encoded by a labeled-line code. Second, neuronal discharges of selective neurons proved to be relevant for the crows' correct performance; if the neurons did not properly encode their preferred numerosity, the crow was prone to make mistakes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The numerosity code found in the crow endbrain is surprisingly reminiscent of findings for neurons in the monkey PFC and posterior parietal cortex (PPC) . In monkeys that discriminated visual numerosity in dot arrays (Eiselt and Nieder, 2013;Jacob and Nieder, 2014;Ott et al, 2014;Viswanathan and Nieder, 2015;Ott and Nieder, 2016;Ramirez-Cardenas et al, 2016;Nieder, 2016b), enumerated numerosity sequentially one by one in visual displays (Nieder et al, 2006), or performed hand movements (Sawamura et al, 2002(Sawamura et al, , 2010, tuned numerosity detectors were found. In the macaque PFC, neurons were also tuned supramodally to numerosity; that is, regardless of whether visual dots or acoustic sounds had to be assessed across time (Nieder, 2012).…”
Section: Labeled-line Codementioning
confidence: 99%
“…But how is numerical information represented in vertebrates that lack a six-layered neocortex? Birds show elaborate quantification skills (Bogale et al, 2011;Scarf et al, 2011;Moll and Nieder, 2014), but their cognitive endbrain structures developed from different pallial precursors compared with mammals, which led to a distinct anatomical layout of the avian endbrain (Jarvis et al, 2005;Butler et al, 2011). Recently, we have shown that neurons in the nidopallium caudolaterale (NCL) of crows, an associative endbrain structure in birds (Divac et al, 1985;Güntürkün, 2005), respond systematically to the presentation of small numerosities from one to five items (Ditz and Nieder, 2015).…”
Section: Introductionmentioning
confidence: 99%